Scenario Modelling for Reproducing Investment Potential of Institutional Sectors in the Regions of the Siberian Federal District - I. V. Naumov; A. V. Trynov; A. O. Safonov (Финансы: теория и практика)
The authors analyze the trends and patterns for reproducing investment potential of institutional sectors. This is relevant for the economic and financial security of territorial systems. The aim of the study is to design a scenario model for reproducing investment potential of institutional sectors at the regional level. This model suggests systems of predictive scenarios for the reproduction and choosing the optimal one to achieve positive dynamics of the socio-economic development of the regions. When designing the scenario model, the authors used statistical methods for data collecting and processing, regression analysis with the least squares method and ARIMA forecasting. The authors developed an algorithm of scenario modelling for reproducing investment potential of institutional sectors in regional systems. The authors designed a balance model for financial flows between them for various investment instruments. They analysed the regularities of reproducing their investment potential. The paper presents an econometric analysis of financial flows among the sectors considering the impact factors, and the basic scenarios of reproducing their investment potential. The work reveals a stable trend of the outflow of investment resources in institutional sectors accumulated by the banking sector abroad during periods of economic downturns and the development of financial and economic crises. The study suggests a model allowing to determine the most likely forecast scenarios for reproducing investment potential of institutional sectors: inertial, extremely negative (pessimistic) and the most favorable (optimistic). The authors conclude that an increase in volatility in financial markets, a weakening of the domestic currency, and an increase in negative trends in economic development significantly increase the likelihood of a pessimistic scenario. To prevent this, the Central Bank of the Russian Federation, must change its policy of regulating the financial and economic activities of the banking sector: to limit the speculative activities of credit institutions that facilitate the withdrawal of financial resources from the domestic economy, to support investment programs for developing of enterprises of the real sector. The prospect for further research is building a system of mechanisms for transiting to the implementation of the optimal scenario of reproducing investment potential of institutional sectors, ensuring the restoration and progressive socio-economic development of territorial systems.